2008
DOI: 10.1038/cgt.2008.30
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric adenoviral vector Ad5/F35-mediated APE1 siRNA enhances sensitivity of human colorectal cancer cells to radiotherapy in vitro and in vivo

Abstract: Apurinic/apyrimidinic endonuclease (APE1), a bifunctional AP endonuclease/redox factor, is important in DNA repair and redox signaling, may be associated with radioresistance. Here we investigate whether targeted inhibition of APE1 can sensitize tumor cells to irradiation in vitro and in vivo. We first constructed chimeric adenoviral vector Ad5/F35 carrying human APE1 siRNA (Ad5/ F35-APE1 siRNA). The infectivity of chimeric Ad5/F35 to LOVO colon cancer cells was greater than that of Ad5. APE1 was strongly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 35 publications
(45 reference statements)
2
73
0
Order By: Relevance
“…Fishel et al reported that human SKOV-3 ovarian cancer cells treated with APE1 siRNA ex vivo and then implanted into female nude mice exhibit a dramatic reduction in tumor volume and cell proliferation during the period of APE1 depletion (51). Moreover, Xiang et al found that LOVO colon cancer cells injected subcutaneously into nude mice and subsequently treated with APE1-specific siRNA adenoviral particles display reduced tumor growth, particularly when challenged with Xray irradiation, relative to the controls (237). Using this established approach, the Wang group has since shown that in vivo APE1 depletion sensitizes A549 non-small cell lung cancer xenografts to hematoporphyrin derivative-mediated photodynamic therapy (243) and human hepatocellular carcinoma cell lines to radio-therapy (32).…”
Section: Protein Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishel et al reported that human SKOV-3 ovarian cancer cells treated with APE1 siRNA ex vivo and then implanted into female nude mice exhibit a dramatic reduction in tumor volume and cell proliferation during the period of APE1 depletion (51). Moreover, Xiang et al found that LOVO colon cancer cells injected subcutaneously into nude mice and subsequently treated with APE1-specific siRNA adenoviral particles display reduced tumor growth, particularly when challenged with Xray irradiation, relative to the controls (237). Using this established approach, the Wang group has since shown that in vivo APE1 depletion sensitizes A549 non-small cell lung cancer xenografts to hematoporphyrin derivative-mediated photodynamic therapy (243) and human hepatocellular carcinoma cell lines to radio-therapy (32).…”
Section: Protein Depletionmentioning
confidence: 99%
“…Hyper-sensitivity of APE1 KD cells has been reported for other clinical DNA-damaging agents, including ionizing radiation (32,150,237), bleomycin (56,170,218), gemcitabine (239), cisplatin (222,246), etoposide (185,221), and photodynamic therapy (236,243). While in some cases it is not obvious what role APE1 would play in repairing the direct DNA damage (e.g., for the crosslinking agent cisplatin), some level of oxidative stress is involved in most genotoxin exposures.…”
Section: Protein Depletionmentioning
confidence: 99%
“…The APE1 siRNA expression vector, entitled Ad5/F35-APE1 siRNA, constructed by De-Bing Xiang, could inhibit APE1 expression and AP endonuclease activity in a dosedependent manner (13). In this study, APE1 was supressed from 80 to 95% at doses of 20-40 MOI Ad5/F35-APE1 siRNA.…”
Section: Cell Cycle Perturbations Aftermentioning
confidence: 67%
“…The APE1 siRNA expression vector named Ad5/F35-APE1 siRNA was constructed by De-Bing Xiang (13). The titer was 1.6x10 10 IU/ml after amplication and purfication.…”
Section: Methodsmentioning
confidence: 99%
“…Double negative APE1 mutation expression is associated with enhanced cytotoxicity to antimetabolites and alkylating agents (McNeill et al 2009). Downregulation of APE1 using an adenoviral vector in a colon cancer mouse model successfully reduced APE1 expression levels and was associated with an increased response to ionising radiation (Xiang et al 2008). This evidence highlights the therapeutic potential of targeting APE1 with small molecular inhibitors to improve radio-and chemotherapeutic efficiency.…”
Section: Ape1 Depletion Hypersensitises Cells To Dna Base Damagementioning
confidence: 89%